Evaluation of the malaria case management in Gokwe South, a pre-elimination district in Midlands Province, Zimbabwe, 2023: A descriptive cross-sectional study - Plassey Ropafadzo Chinove; Mary Muchekeza; Notion Gombe; Gerald Shambira; Addmore Chadambuka; Tsitsi Juru; Gibson Mandozana; Mufuta Tshimanga (Journal of Interventional Epidemiology and Public Health)
Introduction: In Zimbabwe, malaria continues to be a major public health problem. Gokwe South, a malaria pre-elimination district, failed to meet targets in malaria case management indicators, case investigation (44%), cases with microscopy (34%), and cases given primaquine (51%). We evaluated the performance of malaria case management in Gokwe South district in 2023.